Current Scintigraphic Imaging of Lung Cancer - Balci, Tansel Ansal (Bentham Science Publ, 2013)
In recent years, conventional scintigraphical techniques are rarely used in lung cancer patients except the whole body bone scanning and preoperative quantitative lung scintigraphy. With the introduction of positron emission tomography (PET) and more recently PET/CT, management of the lung cancer patients and of the patients with solitary pulmonary nodule has extremely changed from diagnosis to prognosis. The combination of PET with CT scanning allows the integration of metabolic and morphological image information. Nowadays, PET/CT is an accepted modality for lung cancer patients, for many cancer patients, in terms of diagnosis, staging, therapy/radiotherapy planning, prognostic prediction, response monitoring and assessment of recurrence, and becomes widespread throughout the world. In this chapter PET and PET/CT are mainly mentioned as the up-to-date nuclear medicine modalities for diagnostic and therapeutic management in lung cancer.
Keywords: Lung cancer; nuclear medicine; scintigraphy; preoperative evaluation; positron emission tomography; PET; PET/CT; fluorodeoxyglucose; FDG; standard uptake value; SUVmax; solitary pulmonary nodule; diagnosis; staging; therapy response; metastasis; recurrence; residual tissue assessment; survival assessment; radiation therapy planning; tumour hypoxia; neuroendocrine lung cancer